Nationwide study on the use of intravascular catheters in internal medicine departments. Issue 2 (June 2015) - Guembe, M.; Pérez-Granda, M.J.; Capdevila, J.A.; Barberán, J.; Pinilla, B.; Martín-Rabadán, P.; Bouza, E.; ,
Summary: Background: The use of intravascular catheters (IVCs) in intensive care units (ICUs) has been well assessed in recent years. However, a high proportion of these devices are placed in patients outside the ICU, particularly in internal medicine departments (IMDs), where data on the quality of care are scarce. Aim: To assess the use and management of IVCs in IMDs in Spain. Methods: We performed a point prevalence study of all adult inpatients on 47 IMDs from hospitals of different sizes on one day in June 2013. A local co-ordinator was appointed to assess patients and collect data from each site. Findings: Out of the 2080 adult patients hospitalized on the study day, 1703 (81.9%) had one or more IVCs (95.4% of which were peripheral devices). Infection was detected at the insertion site in 92 catheters (5.0%); 87 patients (5.2%) had signs of sepsis, but only one case was considered to be catheter-related. The local co-ordinators estimated that 19% of the catheters in place were no longer necessary. A daily record of the need for a catheter was available in only 40.6% of cases. Conclusion: Our study shows clear opportunities for improvement regarding catheter use and care in Spanish IMDs. Strategies similar to those applied in ICUs should be implemented in IMDs.